Rare Earth Doped Apatite Nanomaterials for Biological Application. (19th March 2015) - Perera, Thalagalage Shalika Harshani; Han, Yingchao; Lu, Xiaofei; Wang, Xinyu; Dai, Honglian; Li, Shipu
Abstract : In most biological analyses, a sensitive detection technique is primarily dependent on the fluorescence labeling agent. New generation of fluorophores called rare earth doped apatite nanoparticle (REAnp) has the ability to emit near infrared radiations which are of low absorptivity by tissue chromophores and especially suitable for biological system imaging. Moreover, bioapatite is demonstrated to be an excellent candidate for biomedical applications because of its biocompatibility, biodegradability, and bioactivity. During recent years a lot of efforts have been made for achievement of REAnp for medical diagnostics and targeted therapeutics applications. In this review, we discuss the significance of REAnps in biological systems, different root of synthesis, and biological applications. Also we discuss the future studies for the effective biological applications of REAnps.